Creative Thinking Ability of Elementary School Students Based on Learning Models - Smith, George; Alhama Najwa, Nibras; Kuncoro, Tri; Alfan, Muhammad (KnE Social Sciences, 2023)
This research was conducted to determine the improvement of students low-creative thinking skills with the help of conventional learning models. Especially in high school students in elementary school. Considering that creative thinking skills are the main thing in 21st, students need to develop their creative thinking skills. In the learning process, a teacher can determine the appropriate learning model according to the learning objectives. This research method uses a qualitative type of literature review. The low-creative thinking skills of students requires a teacher to determine the right learning model so that students get a positive impact. The purpose of this research is to see the effect of the learning model on creative thinking skills; therefore, it is necessary to test the students to determine what learning models can support the mathematical creative thinking skills of elementary school students. Learning models used to support mathematical creative thinking skills include discovery learning, project-based learning, picture to picture, and mind mapping. Moreover, there seems to be an influence of these learning models on the creative thinking skills of the elementary school students. Although there are shortcomings in each learning model, efforts can still be made to maximize each learning model. Keywords: creative thinking, learning models